THE INFLUENCE OF INTERNAL COMMUNICATION AND TEAMWORK ON EMPLOYEE PERFORMANCE IN THE MICROWAVE DISMANTLE PROJECT DIVISION PT. PANCA KARSA SEJAHTERA BEKASI CITY - Sari, Melur; Indrajaya, Titus; Nurminingsih (Transpublika Publisher, 2023)
Within PT. Panca Karsa Sejahtera, specifically the Division Project Dismantle Microwave, recurrent challenges have surfaced including one-sided communication from superiors to subordinates, fragmented team responsibilities becoming individual tasks, and dwindling work targets. Addressing these concerns, this study aims to investigate the relationship of internal communication, teamwork, and employee performance. This study was conducted in Bekasi City, which employs a quantitative approach with total sampling of 100 respondents and employed Structural Equation Modeling (SEM) using smartPLS Version 3 for analysis. Findings reveal that while internal communication positively influences employee performance, its statistical significance is limited. In contrast, teamwork significantly and positively impacts employee performance, while internal communication also significantly enhances teamwork. Effective internal communication is advised for streamlined workflow, and optimizing employee performance requires tailored skill training. Encouraging teamwork through training and active participation is recommended for improved performance. This study offers actionable insights for refining operations and elevating employee performance in the Division Project Dismantle Microwave.